Analisis Kebijakan Dividen Sebagai Variabel Moderasi Pada Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Multifinance - Intan Oxtavian Kusuma Wardany (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to determine and analyze the effect of liquidity, leverage, and profitability on firm value simultaneously and partially, with dividend policy as a moderating variable. For the 2018-2022 timeframe, this research was conducted on multi-finance companies listed on the Indonesia Stock Exchange. The population of this study consisted of 19 companies. The sample was selected using a purposive sampling strategy, and a sample of 13 companies was obtained with 5 years of observation, resulting in 65 research data. However, there are outlier data so that 64 research data are obtained. In this study, the hypothesis testing method was carried out using a panel data regression model with the Random Effect Model approach and for testing the moderating variable using the Moderated Regression Analysis (MRA) model. Data analysis of the two models using the EViews program version 10. The results showed that 1) liquidity had a positive and insignificant effect on company value, 2) Leverage had a negative and insignificant effect on company value, 3) Profitability had a positive and significant effect on company value, 4) Dividend policy was unable to moderate (weaken) the effect of liquidity on company values, 5) Dividend policy is not able to moderate (weaken) the effect of leverage on company value, and 6) Effect of profitability on company value. Keywords : Dividend Policy, Firm Value, Liquidity, Leverage, Profitability